A modified semi-selective medium for isolation and enumeration of Pochonia chlamydosporia (Goddard) Zare & W. Gams: A semi-selective medium for Pochonia chlamydosporia - Rincy, M K; Praveena, R; Eapen, S J (Journal of Spices and Aromatic Crops, 2021)
Pochonia chlamydosporia, is one of the most promising biological control agents for managing phytoparasitic nematodes. Isolation and enumeration of viable colonies of P. chlamydosporia from soil and other substrates without contamination is a major limitation, when commonly available nutrient media are used. Development of a suitable selective/semi-selective media by incorporating one or more inhibitors of microbial growth can facilitate isolation of the fungus. In vitro studies were carried out to test the compatibility of commonly used pesticides, namely, metalaxyl, metalaxyl-mancozeb, carbendazim, copper oxychloride, and chlorpyrifos with P. chlamydosporia. The fungus showed relatively high tolerance to higher doses of metalaxyl and carbendazim and was used in the modified medium for better suppression of other soil borne fungi. In the present study, Kerry’s semi-selective medium was modified and evaluated by counting the viable fungal propagules in different substrates (rice, farmyard manure, maize, rice bran, barley, and sorghum) and soil artificially inoculated with the fungus. The results showed that the modified Kerry’s semi-selective medium can effectively be used for isolation and quantification of P. chlamydosporia in routine studies.